Rumah Hj Abdul Rahim, Jalan Petani, Tanjong, Kuala Trengganu - Amer Hamzah Md. Yunus; Badariah Adnan; Lim, Guat Lee; Muhammad Abd. Latiff; Mohd. Samin Yatim; Roslan Mohd Salleh; Safiah Esa; Wong, Kok Onn; Zaleha Suleiman (KL : UTM, 1977)
Kajian topikal (Fakulti Alam Bina) --Universiti Teknologi Malaysia, 1977